2012
DOI: 10.5511/plantbiotechnology.12.0515a
|View full text |Cite
|
Sign up to set email alerts
|

Upgraded genomic information of <i>Jatropha curcas</i> L.

Abstract: In order to upgrade the genome sequence information of J. curcas L., we integrated de novo assembly of a total of 537 million paired-end reads generated from the Illumina sequencing platform into the current genome assembly which was obtained by a combination of the conventional Sanger method and the Roche/454 sequencing platform. e total length of the upgraded genome sequences thus obtained was 297,661,187 bp consisting of 39,277 contigs. e average and N50 lengths of the generated contigs were 7,579 bp and 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
95
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(97 citation statements)
references
References 18 publications
2
95
0
Order By: Relevance
“…The whole genome of jatropha has been sequenced using a combination of Sanger, pyrosequencing, and Illumina sequencing methods [14, 15]. The total length of the final genomic sequences is 297.7 Mb which covers 72–78% of the expected whole genome (380~410 Mb) of jatropha.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The whole genome of jatropha has been sequenced using a combination of Sanger, pyrosequencing, and Illumina sequencing methods [14, 15]. The total length of the final genomic sequences is 297.7 Mb which covers 72–78% of the expected whole genome (380~410 Mb) of jatropha.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Eswaran et al [18] reported 1,240 ESTs generated from root cDNA libraries of jatropha grown at different drought conditions. Hirakawa et al [14] further assembled all these public available jatropha EST sequences together with their own data, resulting in a total of 30,203 genes, 17,575 transposon related genes, and 2,124 putative pseudogenes. With the advent of low-cost next generation sequencing (NGS) technologies, transcriptome analysis through NGS has become a fast and powerful approach for genome-wide gene discovery and molecular marker development [1921].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the genome of J. curcas (Sato et al, 2011;Hirakawa et al, 2012) reveals that it contains three putative full-length diterpene synthases, which are clustered. Prior to the release of (A) Gas chromatograph obtained with expression of casbene synthase only (lower, black), casbene synthase and CYP726A14 (middle, red), and casbene synthase plus CYP726A14 and CYP726A16 (upper, blue).…”
Section: Clustering Of Diterpenoid Biosynthetic Genes Is Common In Thmentioning
confidence: 99%
“…Jatropha genome data were obtained from release 4.5 of the Jatropha curcas genome database (Sato et al, 2011;Hirakawa et al, 2012). Partial and full-length cDNA sequences for Euphorbia peplus homologs of diterpene synthase and cytochrome P450s were obtained from the PhytoMetaSyn database (Xiao et al, 2013).…”
Section: In Silico Genome Analysis and Phylogenetic Tree Constructionmentioning
confidence: 99%
“…Ty1-copia retrotransposons are flanked at both ends by LTRs, which are structures essential for transposition and are conserved between LTR retrotransposons within the same family . Various families of Ty1-copia elements have been identified in plant species (He et al, 2010;Weber et al, 2010;Wicker and Keller, 2007) and were found to make up a significant proportion of plant genomes (Hirakawa et al, 2012;Wicker et al, 2009).…”
Section: Introductionmentioning
confidence: 99%